2018
DOI: 10.1016/j.celrep.2018.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Basal Suppression of the Sonic Hedgehog Pathway by the G-Protein-Coupled Receptor Gpr161 Restricts Medulloblastoma Pathogenesis

Abstract: SUMMARY Sonic hedgehog (Shh) determines cerebellar granule cell (GC) progenitor proliferation and medulloblastoma pathogenesis. However, the pathways regulating GC progenitors during embryogenesis before Shh production by Purkinje neurons and their roles in tumorigenesis remain unclear. The cilium-localized G-protein-coupled receptor Gpr161 suppresses Shh-mediated signaling in the neural tube. Here, by deleting Gpr161 in mouse neural stem cells or GC progenitors, we establish Gpr161 as a tumor suppressor in Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 46 publications
1
50
0
Order By: Relevance
“…Two other cilia based tumor regulators have been recently identified for Shh‐dependent medulloblastoma . First, the GTPase ADP ribosylation factor‐like 13b (ARL13b) is specifically expressed in PC and a widely used marker for PC.…”
Section: Pc In Brain Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Two other cilia based tumor regulators have been recently identified for Shh‐dependent medulloblastoma . First, the GTPase ADP ribosylation factor‐like 13b (ARL13b) is specifically expressed in PC and a widely used marker for PC.…”
Section: Pc In Brain Cancersmentioning
confidence: 99%
“…Second, the G‐protein‐coupled receptor Gpr161 has been described as a negative regulator of the Hh pathway . Shimada and colleagues found that conditional depletion of Gpr161 in GNPs or neural stem cells induces their hyperproliferation in a PC‐dependent manner leading to spontaneous formation of cerebellar tumors in mice . Gene expression profiling of those tumors revealed a Shh medulloblastoma subtype signature.…”
Section: Pc In Brain Cancersmentioning
confidence: 99%
“…In addition, whether SMO activation reduces ciliary cAMP remains controversial (Jiang et al, 2019;Moore et al, 2016;Tschaikner et al, 2020). Finally, mouse knockouts of βarrestin1/2 (Zhang et al, 2010), EVC2 (Zhang et al, 2015a), or GPR161 (Hwang et al, 2018;Mukhopadhyay et al, 2013;Shimada et al, 2018), fail to exhibit the severe, widespread developmental defects expected with disruption of core Hh pathway components (Goodrich et al, 1996;Tuson et al, 2011;Zhang et al, 2001). Therefore, existing models neither fully explain how SMO activates GLI, nor rule PKA in or out as a mediator of this process.…”
Section: Discussionmentioning
confidence: 99%
“…The best studied of these is GPR161 (described above), which reduces the sensitivity of target cells to HH ligands, likely by activating Gαs and consequently PKA activity (Mukhopadhyay et al, 2013;Pusapati et al, 2018b). GPR161 has been shown to attenuate HH signaling in the developing limb, skeleton and spinal cord, and deletion of GPR161 in neural stem cells can induce cerebellar tumors Mukhopadhyay et al, 2013;Shimada et al, 2018). A ligand that regulates GPR161, positively or negatively, remains to be identified.…”
Section: Regulation Of the Gli Transcription Factors By A Multi-site mentioning
confidence: 99%